2020
DOI: 10.1108/jea-01-2020-0022
|View full text |Cite
|
Sign up to set email alerts
|

Principals' systems thinking attribute: exploring a principal–middle leader relational demography perspective

Abstract: PurposeRelying on information processing and attribution theories, which relate to the formation of leadership perceptions and attributes, the current study seeks to examine the relationship between demographic variables and principals' systems thinking (PST) in an integrated model. The present study purpose was threefold: first, the study seeks to examine whether attributions middle leaders make about PST may show substantial and systematic variance in a management team. Second, the study seeks to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…This is in line with leadership literature that has treated leader personality attributes and behavior as independent explanations of a leader's influence on team and organizational outcomes (Antonakis and Day, 2017). In this regard, scholars have emphasized the influence of relational demography variables similarity between leaders and followers on followers' attributes (Benoliel et al, 2020). As the present sample involves mostly female principals, future research can investigate the differential Specifically, first, regarding the association of the principal personality traits and boundary activities, the association between extraversion and principals' external boundary behaviors is worth discussing.…”
Section: Discussionsupporting
confidence: 77%
“…This is in line with leadership literature that has treated leader personality attributes and behavior as independent explanations of a leader's influence on team and organizational outcomes (Antonakis and Day, 2017). In this regard, scholars have emphasized the influence of relational demography variables similarity between leaders and followers on followers' attributes (Benoliel et al, 2020). As the present sample involves mostly female principals, future research can investigate the differential Specifically, first, regarding the association of the principal personality traits and boundary activities, the association between extraversion and principals' external boundary behaviors is worth discussing.…”
Section: Discussionsupporting
confidence: 77%
“…Recent research suggests that PST may influence the SMT as a whole and have an impact on teamwork processes and outcomes (McCaughan and Palmer, 2018). Based on this, researchers have recommended investigating the relationship between PST and various SMT characteristics to avoid making a fallacy of the wrong level in nested data involving individuals embedded in teams and school organizations (Benoliel et al ., 2021).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…A recent study conducted by Benoliel et al . (2021) found that it is both appropriate and important to examine the effects of PST at the group level.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation